2005
DOI: 10.4049/jimmunol.175.7.4761
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Ongoing Disease in a Nonhuman Primate Model of Multiple Sclerosis by a Human-Anti-Human IL-12p40 Antibody

Abstract: IL-12p40 is a shared subunit of two cytokines with overlapping activities in the induction of autoreactive Th1 cells and therefore a potential target of therapy in Th1-mediated diseases. We have examined whether ongoing disease in a nonhuman primate model of multiple sclerosis (MS) can be suppressed with a new human IgG1κ Ab against human IL-12p40. Lesions developing in the brain white matter were visualized and characterized with standard magnetic resonance imaging techniques. To reflect the treatment of MS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 37 publications
(51 reference statements)
2
40
0
Order By: Relevance
“…Results from recent studies suggest that IL-23, rather than IL-12, is involved in the pathology of many autoimmune diseases, such as multiple sclerosis, inflammatory bowel disease and rheumatoid arthritis [32,33]. Besides its role in the regulation of the Th1 response, IL-23 has also been implicated in the development of a highly pathological memory T cell from naïve T cells (Th17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from recent studies suggest that IL-23, rather than IL-12, is involved in the pathology of many autoimmune diseases, such as multiple sclerosis, inflammatory bowel disease and rheumatoid arthritis [32,33]. Besides its role in the regulation of the Th1 response, IL-23 has also been implicated in the development of a highly pathological memory T cell from naïve T cells (Th17).…”
Section: Introductionmentioning
confidence: 99%
“…Like IL-12, IL-23 and IL-27 are produced predominantly by macrophages and dendritic cells and, together with IL-12, drive the Th1 response [28]. IL-12/23 is now believed to play a crucial role in inflammation and development of autoimmune diseases, since blocking of IL-12 p40 expression or knocking out of the p40 gene appears to prevent inflammation in various disease models [29][30][31].Results from recent studies suggest that IL-23, rather than IL-12, is involved in the pathology of many autoimmune diseases, such as multiple sclerosis, inflammatory bowel disease and rheumatoid arthritis [32,33]. Besides its role in the regulation of the Th1 response, IL-23 has also been implicated in the development of a highly pathological memory T cell from naïve T cells (Th17).…”
mentioning
confidence: 99%
“…B10.PL mice were immunized with MBP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and were treated with vehicle or WAY-196025 100 mg/kg, s.c., once per day for 8 d, and their spleens were isolated. APCs were isolated from these vehicle-treated or WAY-196025-treated B10.PL mice by positive selection magnetic beads to remove CD4 + and CD8 + T cells, using the manufacturer's protocol (Invitrogen Life Technologies).…”
Section: Crisscross Experimentsmentioning
confidence: 99%
“…Naive anti-MBP TCR transgenic CD4 + T cells were isolated by negative selection using magnetic sorting, according to the manufacturer's protocol (Invitrogen Life Technologies). For proliferation assay, APCs were irradiated at 2000 rads and cultured with naive anti-MBP TCR transgenic CD4 + T cells in a ratio of 5:1 in presence of various amounts of MBP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] peptide with or without TGF-b (10 ng/ml). Forty-four to forty-eight hours after the initiation of cultures, supernatant was harvested, and the cultures were pulsed with 0.5 mCi […”
Section: Crisscross Experimentsmentioning
confidence: 99%
“…This evidence indicates that the CM is useful as a model to analyze human immune disease. In fact, the CM has been used to establish an experimental autoimmune encephalomyelitis (EAE) model animal and multiple sclerosis (MS) model animal, and recently an animal model of neuronal diseases (10)(11)(12). For the allergy, no detailed research has been reported, but we developed a CM-specific anti-CD117 monoclonal antibody and identified CD117+ mast cells of CM that play key roles in allergy and anaphylaxis (13).…”
Section: Introductionmentioning
confidence: 99%